2008
DOI: 10.1002/ajmg.b.30736
|View full text |Cite
|
Sign up to set email alerts
|

Association of PIP5K2A with schizophrenia: A study in an indonesian family sample

Abstract: PIP5K2A variants have been shown to be associated with schizophrenia in Caucasian populations. This study tested 12 PIP5K2A SNPs for association with schizophrenia in a sample of 152 sib-pair families of Indonesian descent. All SNPs had previously been tested for association with schizophrenia in a German family sample by Schwab et al. [2006; Mol Psychiatry] and seven SNPs were nominally associated with schizophrenia in this previous study. The purpose of the study was to examine whether previously implicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…We failed to detect association of PIP4K2A in case-control analyses, irrespective of disease severity (data not shown). Our study further corroborated to existing evidence for involvement of PIP4K2A gene in schizophrenia disease and it was in conformity with other association studies where, major alleles of variants were found to be over-represented in disease individuals as compared to control [17], [50], [51]. Phased haplotype and diplotype are more informative and have high statistical power for an association than single SNP association because SNP do not arise independently; they have intrinsic dependency with one another due to their introduction in genealogical process [52].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We failed to detect association of PIP4K2A in case-control analyses, irrespective of disease severity (data not shown). Our study further corroborated to existing evidence for involvement of PIP4K2A gene in schizophrenia disease and it was in conformity with other association studies where, major alleles of variants were found to be over-represented in disease individuals as compared to control [17], [50], [51]. Phased haplotype and diplotype are more informative and have high statistical power for an association than single SNP association because SNP do not arise independently; they have intrinsic dependency with one another due to their introduction in genealogical process [52].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, major allele ‘T’ of rs10828317 found to be associated with deficit schizophrenia and non-deficit schizophrenia patients in Dutch population [50]. Major allele ‘C’ of another intronic variant rs11013052 was found to be over-transmitted in offspring affected with schizophrenia in Indonesian population [51]. On the contrary, a three-locus haplotype C-G-A (rs10828317-rs746203-rs8341) of minor alleles was found to be associated in Chinese population [53].…”
Section: Discussionmentioning
confidence: 96%
“…We decided to study the PIP5K2A gene, because this gene has repeatedly been shown to be associated with schizophrenia ( Schwab et al, 2006 ; Bakker et al, 2007 ; He et al, 2007 ; Saggers-Gray et al, 2008 ), and the vulnerability to develop TD is related to the likelihood to develop positive symptoms of schizophrenia. In a previous study, we have confirmed this association in the presently studied Caucasian Siberian patients with schizophrenia ( Fedorenko et al, 2013 ), but now we also demonstrated a relationship with the prevalence of TD.…”
Section: Discussionmentioning
confidence: 99%
“…PIP5K2A is involved in many different processes, including signal transduction of G-protein-coupled receptors, cell survival by protection against apoptosis, and the genetic response to oxidative stress ( Van den Bout and Divecha, 2009 ). The PIP5K2A gene has been shown to be associated with schizophrenia in several independent studies ( Schwab et al, 2006 ; Bakker et al, 2007 ; He et al, 2007 ; Saggers-Gray et al, 2008 ; Fedorenko et al, 2013 ). This is possibly related to a similar direct vs indirect pathway MSN hyperactivity explaining positive psychotic symptoms in schizophrenia as well as dyskinesia in TD.…”
Section: Introductionmentioning
confidence: 99%
“…These include: 5q22-q31, where association was recently reported in the interleukin-3 (IL3) gene , which awaits replication; 10p15-q21, where evidence of association in the phophatidyl inositol-phosphate 5 kinase 2a (PIP5K2A) (Schwab et al, 2006) followed by mixed positive He et al, 2007;Saggers-Gray et al, 2008) and negative (Jamra et al, 2006) replication results; 6q21-q22, where association with the trace amine associated receptor 6 (TAAR6, previously known as TRAR4) gene located at 6q23.2 (Duan et al, 2004) has mixed positive (Pae et al, 2008;Vladimirov et al, 2007) and negative (Duan, Du et al, 2005;Ikeda et al, 2005; replications; and 15q13-q14, where evidence for linkage to an evoked potential abnormality common in patients and relatively rare in controls was supported by five additional studies reporting positive linkage evidence for schizophrenia in the same narrow region (Gejman, Sanders, Badner, Cao, & Zhang, 2001;Liu et al, 2001;Tsuang et al, 2001;Xu et al, 2001).…”
Section: Other Chromosomal Regions and Genesmentioning
confidence: 99%